Assessing the Impact of Polio Eradication Initiative and Routine Immunization in Zamfara State, North‑West, Nigeria (Nigerian Journal of Health Sciences, 2023)
Background: Evaluation of effectiveness of polio immunization has to be monitored continuously, particularly in endemic countries so that the immunity status can be precisely and effectively established. The aim of the present study was to determine the seroprevalence of poliovirus antibody in Zamfara State, Nigeria. Materials and Methods: This was a cross-sectional study of children aged 0–59 months. The children were randomly selected across the state. Blood samples collected from the children were tested for the presence of antibodies to poliovirus.Results: Blood samples from 63 (78.8%) of the 80 children had antibodies to all the three poliovirus serotypes. Seventy‑five (93.8%), 68 (85.0%), and 75 (93.8%) of blood samples had antibodies to poliovirus serotypes 1, 2, and 3 respectively. All(100.0%) blood samples from children in the age group of 48–59 months tested positive for poliovirus. All(100.0%) the females had poliovirus antibody. In general, poliovirus antibody prevalence increased with increase in oral polio vaccine doses received. Urban children had higher poliovirus antibody prevalence of 81.0%, higher than their rural counterpart. Children whose fathers were educated up to tertiary level had 100.0% poliovirus antibody. There was no association among seroprevalence of poliovirus antibody and number of vaccine doses received and location of child’s place of residence. Prevalence of poliovirus antibody was statistically significant based on age and father’s educational level (χ² = 0.1360, χ² = 0.2923, respectively, P< 0.05). Conclusion: For the state to sustain the gains made in interrupting poliovirus transmission, more work need to be done so as to close the gap observed in the study